Evaluation of plasma anti-GPL-core IgA and IgG for diagnosis of disseminated non-tuberculous mycobacteria infection - Nithichanon, Arnone (PLoS One, 2020)
Detection of IgA antibody against Mycobacterium avium complex (MAC) glycopeptidolipid (GPL) has recently been shown to improve the diagnosis of MAC pulmonary disease but has yet to be tested in disseminated Non-tuberculous mycobacteria (NTM) infection. In this study, we address the diagnostic efficacies of an anti-GPL-core ELISA kit in disseminated lymphadenopathy patients positive for NTM culture and anti-IFN-γ autoantibodies. The study was conducted in a tertiary referral center in northeastern Thailand and patients with NTM, tuberculosis, melioidosis, and control subjects were enrolled. Plasma immunoglobulin A (IgA) and G (IgG) antibodies against GPL-core were detected in the subjects and the specificity and sensitivity of the assay was assessed. Anti-GPL-core IgA and IgG levels were significantly higher in NTM patients than other groups (p < 0.0001). Diagnostic efficacy for NTM patients using anti-GPL-core IgA cut-off value of 0.352 U/ml showed good sensitivity (91.18%) and intermediate specificity (70.15%). Using a cut-off value of 4.140 AU/ml for anti-GPL-core IgG showed the same sensitivity (91.18%) with increased specificity (89.55%) and an 81.58% positive predictive value. Most patients with moderate levels (4.140–7.955 AU/ml) of anti-GPL-core IgG had rapidly growing mycobacteria (RGM) infection. Taken together, the detection of anti-GPL-core antibodies could provide a novel option for the diagnosis and management of disseminated NTM infected patients.